Design of an Iterative Multi-Analytical Fuzzy TOPSIS Framework for Enhancing Electoral Decision Systems in India: Interpretability, Regional Adaptation, and Policy Simulations (Statistics, Optimization & Information Computing, 2025)
The integrity, transparency, and inclusivity of the voting systems in India need to be empowered by the diverse demographics of the nation and the complex manner in which socio-economic and political factors interact towards influencing electoral behavior. Traditional voting analysis frameworks often rely on rigid statistical models that fail to capture the ambiguity inherent in human decision-making, especially in terms of subjective judgments and linguistic assessments. Existing models, therefore, remain unfit for purposes of policy-level decision support, owing to factors of lack of temporal adaptability, regional granularity, and scalable validation mechanisms. To remedy these limitations, this study proposes the development of a novel multi-methodological framework based on Fuzzy TOPSIS, augmented with five novel analytical extensions for model implementation and validation. The Explainable Causal Inference Layer integrated with Fuzzy TOPSIS (XCI-FTOPSIS) stands for traceable and interpretable prioritization of preferences by voters. The Spatiotemporal Attention-Based Fuzzy Decision Matrix (SA-FDM) captures governance preferences evolving over timestamp and region. The Deep Belief Network-enhanced Fuzzy Consensus Evaluation (DBN-FCE) consolidates expert weight consistency. The Social Simulation-driven Fuzzy Governance Metrics (SS-FGM) run simulation scenarios for policy changes. Finally, the Multilevel Hierarchical Bayesian Aggregation for Fuzzy Outputs (MHBA-FO) provides consistent aggregation of perspectives across district, state, and national levels. This integrated approach also reinforces the interpretability and validity of governance ranking models in the process. This is done with the added attribute of adaptability and scalability for application in real-world situations. Furthermore, the suggested system provides strategic toolkits for the use of policymakers. This is done along with electoral authorities to optimize governance-related issues in process. Along with enhanced voter engagement, and assure data-centric inclusivity into democratic processes